Long-term systematic profiling of dust aerosol optical properties using the EOLE NTUA lidar system over Athens, Greece (2000–2016). (June 2018) - Soupiona, O.; Papayannis, A.; Kokkalis, P.; Mylonaki, M.; Tsaknakis, G.; Argyrouli, A.; Vratolis, S.
Abstract: We present a comprehensive analysis of the seasonal variability of the vertical profiles of the optical and geometrical properties of Saharan dust aerosols, observed in the height region between 1000 and 6000 m, over the city of Athens, Greece, from February 2000 to December 2016. These observations were performed by a multi-wavelength (355-387-532-1064 nm) Raman lidar system under cloud-free conditions. The statistical analysis (using aerosol monthly mean values) is based on nighttime vertical Raman measurements of range-resolved aerosol optical properties (backscatter and extinction coefficients, lidar ratio, Ångström exponent) at 355 nm (57 dust events during more than 80 measurement hours). We found that the number of dust events was highest in spring, summer, and early autumn periods and that during spring the dust layers were moved at higher altitudes (∼4500 m) than in other seasons. The number of the forecasted dusty days (on monthly basis) by the BSC-DREAM8b model compared to those of the performed lidar measurements were found to have a quite strong correlation (R 2  = 0.81), with a maximum occurrence predicted for the spring season. In the worst case scenario, at least 50% of the model-forecasted dust events can be observed by lidar under cloudless skies over Athens. For the sampled dust plumes we found mean lidar ratios of 52 ± 13 sr at 355 nm in the height range 2000–4000 m a.s.l. Moreover, the dust layers had a mean thickness of 2497 ± 1026 m and a center of mass of 2699 ± 1017 m. An analysis performed regarding the air mass back-trajectories arriving over Athens revealed two main clusters: one pathway from south-west to north-east, with dust emission areas in Tunisia, Algeria and Libya and a second one from south, across the Mediterranean Sea with emission areas over Libya and the remaining part of Algeria and Tunisia. This clustering enabled us to differentiate between the aerosol optical properties between the two clusters, based on their residence time over the Saharan region, the European continent and the Mediterranean Sea. We finally concluded that even if the dust source regions are about the same, the aging and mixing processes of these air masses, passing over different areas, might have an impact on the aerosol optical properties. Graphical abstract: Highlights: Statistical analysis of the seasonal variability of the Saharan dust aerosols arriving over Athens, for the period 2000–2016. Dust aerosol optical and geometrical properties included: baer, aaer, LR, AE a355/a532, zB, zT, t and zCOM . Mean lidar ratios value 52 ± 13 sr at 355 nm. Height range of dust layers was between 2000 and 4000 m (mean value zCOM 2699 ± 1017 m. a.s.l.) The aging of the air masses passing over different areas has an impact on the aerosol optical properties (cluster analysis).